Pengaruh Reward dan Punishment terhadap Kinerja Karyawan PT Business Training and Empowering Management Surabaya - Agung Dwi Nugroho (Universitas Proklamasi 45 Yogyakarta, 2015)
Human resources is one of the most important assets and have a direct impact on an organization or agency should be supported source - other sources of information. One way you can improve the performance of employees is through employee development, namely the holding of reward and punishment. The research problem is whether the reward and punishment influence simultaneously on the performance of employees of PT Business Training And Empowering Management Surabaya, whether rewrad and punisment partially affect the performance of employees of PT Busines Training and Empowering Management Surabaya, and where the most dominant influence between reward and punishment of performance. This study aims to determine the effect of reward and punishment to employee performance and to determine the most dominant pengaruyh the performance of employees of PT Business Training And Management Empowering Surabaya. The test equipment used multiple linear regression analysis with the help of analysis tools SPSS 17.0. From the results of multiple linear regression analysis of the F test shows that the reward and punishment simultaneously significant effect on employee performance. Partially reward (X1) and punishment (X2) effect on the performance of employees of PT PT. Business and Management Training Empowering Surabaya.